Penokohan Cerita Rakyat “Singa Perbangsa” sebagai Media Pembelajaran Kata Sifat dalam BIPA - Cut Nuraini (SAP (Susunan Artikel Pendidikan), 2025)
This study aims to analyze the effectiveness of characterization in the folk tale “Singa Perbangsa” from Karawang Regency in improving the understanding of adjectives for foreign speakers learning Indonesian as a Foreign Language (BIPA). This study also focuses on understanding the moral and cultural values contained in the story, such as wise leadership, courage and responsibility, justice and unity, as well as local wisdom and love for the country. The method used is a quasi-experimental design with two groups, namely the experimental group who learned through folk tale texts and the control group who used general narrative texts. The research subjects consisted of 24 foreign students enrolled in the BIPA program at the Indonesia University of Education. The instruments used included an adjective ability test, observation sheets, and a learning interest questionnaire. The results showed a significant increase in adjective comprehension in the experimental group (p < 0.05) with an average increase of 30%, compared to the control group, which only increased by 12%. Qualitative analysis showed that the character Singa Perbangsa helped learners understand the use of adjectives in concrete moral and social contexts. This story also served as a means of cultural diplomacy, introducing the noble values of the Karawang community to the international community.